2021
DOI: 10.1038/s41467-021-24386-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting spatial heterogeneity and the immune-evasion mechanism of CTCs by single-cell RNA-seq in hepatocellular carcinoma

Abstract: Little is known about the transcriptomic plasticity and adaptive mechanisms of circulating tumor cells (CTCs) during hematogeneous dissemination. Here we interrogate the transcriptome of 113 single CTCs from 4 different vascular sites, including hepatic vein (HV), peripheral artery (PA), peripheral vein (PV) and portal vein (PoV) using single-cell full-length RNA sequencing in hepatocellular carcinoma (HCC) patients. We reveal that the transcriptional dynamics of CTCs were associated with stress response, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 43 publications
1
89
0
Order By: Relevance
“… 174 , 175 , 176 , 177 Single‐cell sequencing analysis revealed that chemokine CCL5 is an important mediator of CTC immune escape. 162 CCL5 can promote immune escape and metastasis of CTCs by recruiting Tregs, which further suggests that chemokines can promote immune escape. 162 In addition, MDSCs secrete TGF‐β in esophageal cancer, which can increase the expression of PD‐1 on tumor‐infiltrating CD8+ T cells, leading to immunotherapy resistance.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 95%
See 1 more Smart Citation
“… 174 , 175 , 176 , 177 Single‐cell sequencing analysis revealed that chemokine CCL5 is an important mediator of CTC immune escape. 162 CCL5 can promote immune escape and metastasis of CTCs by recruiting Tregs, which further suggests that chemokines can promote immune escape. 162 In addition, MDSCs secrete TGF‐β in esophageal cancer, which can increase the expression of PD‐1 on tumor‐infiltrating CD8+ T cells, leading to immunotherapy resistance.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 95%
“… 158 , 159 These cytokines/chemokines are involved in ECM remodeling, tumor invasion, EMT, angiogenesis, pre‐metastatic niche reprogramming, extravasation, and modulating stromal cells and immune cells. 115 , 154 , 160 , 161 , 162 The cytokines/chemokines including TNF‐α, IL‐8, CCL20, CXCL5, CXCL12. 163 , 164 , 165 , 166 CXCR2, CXCR3, and CXCR4, up‐regulate EMT‐TFs (snail and ZEB1), promote MMP‐2 expression, and accelerate EMT of cancer cells, thereby promoting tumor metastasis.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…Negative-enrichment methods are based on the removal of white blood cells by antibody-based depletion strategies usually based on anti-CD45-coated magnetic beads or CD45 depletion cocktails. Enriched CTCs can be detected afterward by several different methodologies such as immunocytochemistry (ICC) [ 18 , 19 , 20 , 21 , 22 , 23 ], quantitative real-time polymerase chain reaction (PCR) [ 24 , 25 , 26 ], flow cytometry, or immunofluorescence in situ hybridization (iFISH) [ 27 , 28 , 29 , 30 , 31 , 32 ], which may combine several probes or antibodies to identify different CTC subpopulations. In contrast, positive-enrichment methods take advantage of specific biological and physical properties of CTCs to distinguish them from non-tumoral blood cells.…”
Section: Liquid Biopsy and Ctcsmentioning
confidence: 99%
“…The EMT is the process by which a CTC with an epithelial phenotype acquires mesenchymal characteristics that confer increased migratory ability, invasiveness and/or drug resistance, thus contributing to HCC spreading [ 82 ]. The activation of the EMT process in CTCs occurs primarily in the bloodstream and involves dynamic adaptive mechanisms that are associated with stress response, cell cycle, or immune evasion [ 21 , 40 , 83 , 84 ]. This process may not be considered dichotomous: CTCs do not necessarily exist in ‘pure’ epithelial or mesenchymal states.…”
Section: Surface Markers To Identify Ctcs In Hcc and Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation